2022
DOI: 10.1097/j.pain.0000000000002838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pain neuroscience education after breast cancer surgery on pain, physical, and emotional functioning: a double-blinded randomized controlled trial (EduCan trial)

Abstract: Supplemental Digital Content is Available in the Text.Adding 6 sessions of pain neuroscience education to standard physiotherapy after breast cancer surgery did not result in a better course of functioning compared with biomedical pain education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…A0: baseline assessment, A1: postoperative assessment, A4: 4 months post‐surgery assessment (=end of intensive phase), A6: 6 months post‐surgery assessment, A8: 8 months post‐surgery assessment, A12: 12 months post‐surgery assessment, and A18: 18 months post‐surgery assessment (end of maintenance phase). Missing data and reasons are shown for the primary outcome measure of the EduCan trial (pain‐related disability evaluated with Pain Disability Index; Dams et al, 2022). However, there are more missing data for the outcome measure QST in this article.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A0: baseline assessment, A1: postoperative assessment, A4: 4 months post‐surgery assessment (=end of intensive phase), A6: 6 months post‐surgery assessment, A8: 8 months post‐surgery assessment, A12: 12 months post‐surgery assessment, and A18: 18 months post‐surgery assessment (end of maintenance phase). Missing data and reasons are shown for the primary outcome measure of the EduCan trial (pain‐related disability evaluated with Pain Disability Index; Dams et al, 2022). However, there are more missing data for the outcome measure QST in this article.…”
Section: Resultsmentioning
confidence: 99%
“…The present manuscript reports on secondary analyses of the EduCan Trial. Results on the primary analysis are reported elsewhere (Dams et al, 2022). Findings were reported in accordance with the CONsolidated Standards of Reporting Trials (CONSORT) guidelines (Moher et al, 2012; Schulz et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PNE covers topics such as acute versus chronic pain, the purpose of acute pain, the origins of acute pain, the transition to chronic pain and potential factors that sustain chronic pain, explained from a biopsychosocial view rather than a pure patho-anatomical output, and as a consequence, patients’ illness perceptions also change to the biopsychosocial perspective 23 24. Previous single-arm studies using PNE in BCSs showed positive results on central sensitisation symptoms25 26 and pain-related function and quality of life,26 whereas results in a large randomised controlled trial comparing PNE combined with physical activity with biomedically focused education did not find any significant differences in different pain-related outcomes 27. However, the latter trial was conducted in BCSs who were not preselected for having significant pain, which might explain the absence of an added value of the respective PNE-based intervention 27.…”
Section: Introductionmentioning
confidence: 99%
“…It typically involves elucidating the etiological underpinnings and remedial strategies of pain sensitization, promoting patient engagement in rehabilitative exercise and cognitive modi cations. These components collectively contribute to enhanced pain control, improved quality of life, and augmented physical functionality ,Dams 2023]. However, extant PNE frameworks are primarily con gured for chronic pain management and lack speci city for surgical contexts [Landry 2020].…”
Section: Introductionmentioning
confidence: 99%